Review of Various VANET Protocols Using NS-2 Simulator - Jain, Vaishali; Singh Kushwah, Rajendra (International Journal of Computer Sciences and Engineering, 2025)
Vehicular Ad-Hoc Networks are growing field of research. In this network most promising task is provide safety or other application to driver and passenger. It became key component of transportation. In this paper different routing protocol like AODV, DSR and M-DART are studied. At the end of paper outcomes of these protocols are discussed.